Effects of electronic emergency-department whiteboards on clinicians' time distribution and mental workload. (March 2016) - Hertzum, Morten; Simonsen, Jesper
Whiteboards are a central tool at emergency departments. We investigate how the substitution of electronic for dry-erase whiteboards affects emergency department clinicians' mental workload and distribution of their time. With the electronic whiteboard, physicians and nurses spend more of their time in the work areas where other clinicians are present and whiteboard information is permanently displayed, and less in the patient rooms. Main reasons for these changes appear to be that the electronic whiteboard facilitates better timeouts and handovers. Physicians and nurses are, however, in the patient rooms for longer periods at a time, suggesting a more focused patient contact. The physicians' mental workload has increased during timeouts, whereas the nurses' mental workload has decreased at the start of shifts when they form an overview of the emergency department. Finally, the secretaries, but neither physicians nor nurses, access whiteboard information on computers other than the permanent displays.